The Democratic Movement in the World - Ghimire, Tara Nath; Phuyel, Shyam Prasad (Historical Journal, 2023)
This study is related to the democratic movement in the world. The research focuses on the role of the democratic movement and its impact on today for human civilization. This study is prepared about the democratic movement, its achievements, and the essential foundations for democracy. It examines democratic movements from the Magna Carta, the bloodless revolution in Britain, and American independence to the French revolution. The research is reached in conclusion with an attempt to investigate the question of what effect the democratic movement has had on the transformation of the modern era. There were various efforts for the establishment of democracy during the political changes. This is also true that there is standing in the face of problems and challenges from institutionalizing its achievements. Research is focused on democratic movements and their achievements. This study is completely qualitative research in nature. Only secondary material has been used in the study and the available data has been taken out using descriptive and analytical methods.